New Perspectives on Pop Culture (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
While the established qualitative meaning of the term ‘popular culture’ remains pertinent, as superhero comics and pop music, Hollywood films and TV thrillers, and pulp fiction and videogames are still quite naturally assigned to the realm of popular culture and thus excluded from high culture, this Special Issue explores recent shifts from the qualitative to the quantitative dimensions of the popular in order to re-evaluate the significance of the high/low culture difference. The chapters in this reprint reassess the gap between high and low culture in an effort to rethink conventional notions of pop and the popular and acknowledge quantified popularity’s increasing significance as a scalable force in contemporary society.